Application of High-Resolution Trip Trace Stitching to Evaluate Traffic Signal System Changes. Issue 9 (September 2019) - Li, Howell; Mackey, Jamie; Luker, Matt; Taylor, Mark; Bullock, Darcy M.
Second-by-second GPS trajectories, called trip traces, of vehicles moving along an arterial provide the highest fidelity measure of corridor operations. However, large samples of such contiguous trajectories are not always possible because of varying techniques to reset probe vehicle IDs for data privacy, varying probe data penetration rates, and varying vehicle routing. This paper analyzes changes in segment travel time using the Mann–Whitney U test and proposes a method for creating a composite travel time metric using trip trace data. These techniques were applied to a four-corridor signal improvement and upgrade project in southeastern Salt Lake County. The study found that on average three out of the four corridors decreased in composite median travel time, by 32 s, 16 s, and 14 s. Interquartile range (IQR) was used to assess travel time reliability and the IQR travel time reduced (improved) on average by 33 s, 23 s, 18 s, and 1 s. In addition, a rank-sums method for statistically comparing the two composite travel time distributions is applied to the results. The four corridors had a total of 48 links and were evaluated during five time-of-day periods. Out of the 240 link-periods, the rank-sums analysis method found that overall, 68 link-periods improved and 13 link-periods slowed, at a 95% significance level. The annualized user benefit from the improvements was estimated at 2.2 million for the four corridors.